Zinc supplementation increases protein titer of recombinant CHO cells - Capella Roca, Berta (Cytotechnology, 2019)
In order to study the impact of zinc and copper on the titer levels of mAb and recombinant protein in CHO cells, the IgG-expressing (DP12) and EPO-expressing (SK15) cell lines were cultured in chemically defined media with increasing concentrations of either metal. Supplementation with 25 mg/l in CDM media resulted in a significant increase in EPO (1.7-fold) and IgG (2.6-fold) titers compared to control (no added zinc). Titers at this Zn concentration in CDM containing the insulin replacing agent aurintricarboxylic acid (ATA) (CDM + A) showed a 1.8-fold (EPO) and 1.2-fold (IgG) titers increase compared to control. ATA appeared to also reduce the specific productivity (Qp) enhancement induced by Zn-25, with up to 4.9-fold (DP12) and 1.9-fold (SK15) Qp increase in CDM compared to the 1.6-fold (DP12) and 1.5-fold (SK15) Qp increase observed in CDM + A. A 31% reduced Viable Cell Density (VCD) in DP12 was observed in both Zn-supplemented media (3 × 10(6) cells/ml vs 4.2 × 10(6) cells/ml, day 5), whereas SK15 Zn-25 cultures displayed a 24% lower peak only in CDM + A (2.2 × 10(6) cells/ml vs 3.2 × 10(6) cells/ml, day 5). Supplementation with copper at 13.7–20 mg/l resulted in less significant cell line/product-type dependent effects on titer, VCD and Viability. Analysis of the energetic phenotype of both cell lines in 25 mg/l Zn-supplemented CDM media revealed a twofold increase in the oxygen consumption rate (OCR) compared to non-supplemented cells. Together, these data suggest that high zinc supplementation may induce an increase in oxidative respiration metabolism that results in increased Qp and titers in suspension CHO cultures. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10616-019-00334-1) contains supplementary material, which is available to authorized users.